Effects of a Home-Based Family-Centred Early Habilitation Program on Neurobehavioural Outcomes of Very Preterm Born Infants: A Retrospective Cohort Study - Michela Poggioli; Fabrizio Minichilli; Tiziana Bononi; Pasquina Meghi; Paolo Andre; Alessandra Crecchi; Bruno Rossi; Maria Chiara Carboncini; Alberto Ottolini; Luca Bonfiglio (Neural Plasticity)
Preterm children have an increased risk of neurodevelopmental impairments which include psychomotor and language retardation. The objectives of the present retrospective cohort study were to examine the effects of an individually adapted, home-based, and family-centred early developmental habilitation program on neurodevelopmental and behavioural outcomes of very preterm children compared with a standard follow-up at 2 years’ corrected age. Enrolled infants were retrospectively assigned to the intervention group (61 subjects) or to the control group (62 subjects) depending on whether they had or had not carried out a home-based family-centred early developmental habilitation program focused on environmental enrichment, parent-guided environmental interaction, and infant development. Developmental outcome was assessed for both groups at 24 months’ corrected age using the Bayley Scales of Infant Development 2nd Edition. Intervention significantly improved both cognitive and behavioural outcomes. In addition, males had significantly lower scores than females either before or after treatment. However, the treatment was effective in both genders to the same extent. In conclusion, a timely updated environment suitable to the infant’s developmental needs could provide the best substrate where the parent-infant relationship can be practised with the ultimate goal of achieving further developmental steps.